Casuistry of traumatic brain injury in dogs from the perspective of forensic pathology (Research, Society and Development, 2022)
The veterinary pathologist plays a fundamental role in forensic veterinary medicine. The injuries found and the condition that the animal is in can be the result of intentional acts and forensic traumatology is an important tool for the identification of injuries. Traumatic brain injury (TBI) is characterized by physical damage to brain tissue. The objective of this work is to describe the cases of necropsies with forensic purposes of animals that suffered traumatic brain injury as the main process of death. Through a retrospective study of the casuistry of SOVET – UFPel, necropsies with forensic purposes and a history of suspected traumatic brain injury in the period of 11 years were selected. Of the 14 forensic necropsies performed in the period, 5 dogs had a history or suspicion of traumatic brain injury. Most were mixed breed dogs and females,and parietal bone fracture was the most common lesion. Fractures of the occipital bone and superficial injuries to the frontal bone were also observed. Three of the five animals were suspected of aggression by people they were close to, characterizing abuse. Two of the five corpses studied were exhumed, reinforcing the performance of forensic necropsy as an essential tool for elucidating the cause of death, especially in cases of aggression. In conclusion, parietal bone lesions were the most frequent and exhumation is necessary to elucidate cases of suspected abuse. Forensic necropsy is essential to properly record the changes found and establish the causal link in forensic cases.